Application Of AHP On SMED For Jig And Fixture Design Selection - Wan Mahmood, Wan Hasrulnizzam; Mohd Amin, Ahmad Nawawi; Hanapiah, Luqmanulhakim (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
The purpose of this paper is to discuss the application of AHP as a decision-making tool in determining the best design model. Three design models developed were based on the SMED concept which were significant with small manufacturing enterprise jigs and fixtures engineering project., 10 design requirements were considered and used in AHP analysis. The result shows that – the four parameters that were critical measures are gripping, ease of assembly, ease of cleaning and go-no-go inspection, meanwhile easy maintenance was less important for SMED products.